Effect of L-NMMA, cromakalim, and glibenclamide on cerebral blood flow in hypercapnia and hypoxia. - Reid, J; Davies, A; Ashcroft, F; Paterson, D (1995)
Sulfonylureas reduce cerebral blood flow (CBF) during hypoxia but not during hypercapnia, whereas blockers of nitric oxide (NO) synthesis reduce hypercapnic CBF. However, the effect of NO blockers on hypoxic CBF is uncertain. CBF was measured in the cortex of 51 enflurane-anesthetized rats by the hydrogen clearance technique during eucapnia, hypercapnia (arterial PCO2 65 Torr), and hypoxia (arterial PO2 40 Torr). CBF increased twofold in both hypercapnia and hypoxia from eucapnia. Intracortical (ic) NG-monomethyl-L-arginine (L-NMMA, 100 microM-5 mM) attenuated both the hypercapnic and hypoxic dilations by 60-70%, and L-arginine (300 mg/kg iv) partially reversed these effects. Glibenclamide (10 microM ic) and L-NMMA gave no further attenuation of the hypoxic dilation than L-NMMA alone. Cromakalim (10 microM, ic) increased CBF in eucapnia, but this was not seen in the presence of glibenclamide. The adenosine antagonist 8-phenyl-theophylline did not attenuate the hypoxic dilation. This suggests that NO synthesis plays a major role in the regulation of CBF in hypercapnia and hypoxia. But the combined effects of glibenclamide and L-NMMA do not further attenuate CBF in hypoxia.